Regulação emocional e sofrimento mental em trabalhadores brasileiros durante a pandemia de Covid-19 no Brasil - Schmitz, Bruna Sangoi (2022)
The new coronavirus pandemic (COVID-19) has greatly impacted economics and health related fields, with hundreds of million cases confirmed across the globe and a high percentage of fatalities. Besides the aforementioned consequences, the uncertainties related to the virus, as well as the drastic behavioral changes required by isolation and social distance normatives, caused a significant impact on individuals mental health, who are prone to experiment feelings of impotence, fear, anxiety or depression during this period. Workers who are involved in providing services to the public are amongst groups with high risks of infection during COVID19 outbreaks, and when handling such stress caused by this environmental exposition, each individual selects different confrontation strategies. Once confrontation strategies are stress management resources, the way which one regulates one´s emotions may also alter the final repertory, and personality factors may also contribute to the diversity of behavioral responses observed in these individuals’ workplace. The present study aimed to understand the emotional suffering levels reported by those working in services to the public during the COVID-19 pandemic in Brazil, and the role played by emotional regulation and personality traits in this symptomatology. A total of 80 Brazilian workers, mostly between 18 and 24 years old (30.77%) and 30 and 34 years old (26.92%) took part in the study. Participants answered a sociodemographic questionnaire, besides the Reduced Version of Depression, Anxiety and Stress Scale (DASS-21), Reduced Personality Markers (MR-25) and Difficulties in Emotion Regulation Scale (DERS). For data analysis, stepwise regression was used. It was found that only Emotional Regulation is correlated to the report of depression, anxiety and stress symptoms in the studied sample. Furthermore, the study highlights the need to further understand the mediator role played by emotional regulation in the appearance of mental health suffering in Brazilian workers.